Phytotoxicity Study on Bidens sulphurea Sch. Bip. as a Preliminary Approach for Weed Control - Da Silva, Bruna P. [UNESP]; Nepomuceno, Mariluce P. [UNESP]; Varela, Rosa M.; Torres, Ascensión; Molinillo, José M. G.; Alves, Pedro L. C. A. [UNESP]; Macías, Francisco A. (My University, 2017)
Farmers of the Franca region in Brazil observed that Bidens sulphurea was able to eliminate the Panicum maximum weed, which infected coffee plantations, without affecting the crop. In an effort to determine if the inhibitory effects observed were due to the presence of phytotoxic compounds from leaves and roots, a biodirected isolation and spectroscopic characterization has been carried out. The leaf dichloromethane and root acetone extracts were the most active, and the former appeared to be more phytotoxic to the target species, including four weeds. A total of 26 compounds were isolated from leaves and roots, and four of them are described here for the first time. The major compounds in the leaf extract are the sesquiterpene lactones costunolide, reynosin, and santamarine, and these showed marked inhibition. Amaranthus viridis and Panicum maximum were the most sensitive species of the weeds tested. These three phytotoxic lactones were also evaluated on A. viridis and P. maximum under hydroponic conditions. A. viridis was the most affected species with the three lactones, and santamarine was the most phytotoxic compound on both. This is the first time that the phytotoxicity of sesquiterpene lactones has been evaluated on hydroponic culture. The work described here is a preliminary approach for the use of B. sulphurea for weed control in agriculture, both as a cover crop and by use of its components as natural herbicide leads.
Keywords: allelochemicals; allelopathy; Bidens sulphurea; costunolide; hydroponic culture; reynosin; santamarine